Boys are Like Puppies, Girls Aim to Please: How Teachers’ Gender Stereotypes may Influence Student Placement Decisions and Classroom Teaching - Riley, Tasha (Alberta Journal of Educational Research, 2014)
Since teachers’ decisions and behaviour potentially influence learners’ future academic and occupational status, it is imperative that these decisions be unbiased. In the study reported here, 21 teachers were invited to place 24 fictional student record cards into regular, advanced, or supplementary learning assistance classes. Study findings revealed that teachers’ perceptions of the differences between male and female learners were clearly defined and, on some occasions, did influence teachers’ decisions regarding at which achievement level to place student record cards. Findings, as well as the research method employed, may provide teacher educators with useful tools for sensitizing teachers to the implications of their beliefs and biases as well as encouraging awareness toward specific instances of gender stereotyping in the classroom. Puisque le comportement des enseignants et les décisions qu’ils prennent ont le potentiel d’influencer le statut professionnel et académique de leurs élèves, il est crucial que les décisions soient impartiales. Pour cette étude, on a demandé à 21 enseignants de classer 24 élèves fictifs dans des classes régulières, avancées ou avec assistance supplémentaire. Les résultats ont révélé que les perceptions des enseignants relatives aux différences entre les filles et les garçons sont bien définies et qu’à certaines occasions, celles-ci ont influencé leur classement des élèves selon le niveau de rendement. Ces résultats, ainsi que la méthodologie de recherche, pourraient constituer des outils utiles dans la sensibilisation des enseignants quant aux retombées de leurs croyances et leurs préjugés. Ils pourraient aussi favoriser une prise de conscience par rapport à des stéréotypes particuliers liés au genre que l’on retrouve en salle de classe.